Investigating Online Impulse Buying Behavior In South Asian Context - IFTIKHAR, MARRIYAM; IQBAL, DR. JAWAD (The journal of contemporary issues in business and government, 2021)
Drawing on the stimulus-organism-response (S-O-R) paradigm this study focuses on online sales promotion, impulse buying tendency and social influence to examine online impulsive buying behavior of online customers of Pakistan. The study further assesses the mediating role of urge to buy impulsively on the relationship of sales promotion, impulse buying tendency, social influence and online impulse buying behavior. A total 576 questionnaires were distributed to students from four universities of using convenience sampling technique. The study has used SPSS (version 21.0) and PLS-SEM (version 3.2.8) for analyzing data at 0.05 critical level. According to the analysis results all the factors including sales promotion, impulse buying tendency and social influence significant influence on online impulse buying behavior. Results revealed the positive impact of targeted constructs on online impulse buying behavior with mediating role of urge to buy impulsively.The study adds new theoretical linkages and empirical evidences on the interaction between by sales promotion, impulse buying tendency, social influence and online impulse buying behavior with theoretical support of S-O-R Model. Moreover, this study is useful for e-marketers in assisting them to develop appropriate policies and customer-driven strategies by addressing customer’s online impulse buying behavior in south Asian context.